Changing strategy by Turkey’s AKP: the learning curve theory - Mohamad Shukri, Syaza Farhana (SAGE Publications Inc., 2019)
Since 2014, Turkey has been moving towards a heightened sense of nationalism and populism especially after Recep Tayyip Erdogan became the first popularly elected President of Turkey in 2017. His nationalist rhetoric went up compared to when he became Prime Minister over a decade ago when the country was touted as a model of liberalism among Muslim countries. Rather than putting a damper on the party, government, or Erdogan himself, his conservative rhetoric has helped consolidate the government’s power, showcasing the shift in strategy by the Adalet ve Kalkınma Partisi (AKP) during uncertain times. This article borrows from behavioural psychology the concept of the learning curve theory or the S-curve theory to examine this shift in AKP strategy. It is argued that after reaching a political peak with the Gezi Park protest in the summer of 2013, Erdogan is employing a different rhetorical approach—a populist one—to gain more political traction.